The Effect of Corporate Social Responsibility Disclosure on Earnings Management in Energy Sector Companies Listed on the Indonesia Stock Exchange (IDX) for 2019-2021 - Linatul Uyun; Afiq Chamim Mubaroq (Journal of Management Economics and Financial Accounting, 2025)
Financial reports are a tool for measuring management performance in managing a company. The better the financial performance report, the better the company's performance. However, in practice, many companies present their financial reports through several adjustments with the aim of manipulating information through earnings management practices; this is a major factor in financial reporting no longer reflecting the company's core values. The phenomenon of earnings management is carried out in many companies at home and abroad. Disclosure of corporate social responsibility (CSR) is the right step in reducing earnings management practices. This research aims to determine the effect of CSR reports on earnings management in energy sector companies listed on the Indonesia Stock Exchange. Data collection used a purposive sampling technique with predetermined criteria, resulting in a sample of 19 companies used in the research. Test the assistance hypothesis using a multiple linear regression test with SmartPLS 4 software. The research results in Model 1 show that CSR has a positive effect on earnings management, which indicates that the company uses CSR legitimacy to cover up earnings management practices. Meanwhile, model 2 shows that there is no influence between the six categories of CSR disclosure on earnings management.